United Kingdom &Amp; Ireland Computing Education Research Conference. 2020
DOI: 10.1145/3416465.3416476
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Belonging: The Intersectionality of Self-Identified Minority Status and Gender in Undergraduate Computer Science Students

Abstract: Creating inclusive learning environments for all students is of primary importance. Student sense of belonging is an important part of this. However, sense of belonging can show variations according to factors such as ethnicity and gender as well as influencing attributes such as motivation and persistence. We utilised a survey adapted from the "Math Sense of Belonging Scale" to examine the relationship between undergraduate computer science students' sense of belonging, gender identity, and self-declared mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…other than a statistically significant difference between the two groups in how much they socialize with other students (t(30.313) = -5.197, p<0.001). This supports and extends our previous findings [22,23].…”
Section: Intersectionalitysupporting
confidence: 93%
See 4 more Smart Citations
“…other than a statistically significant difference between the two groups in how much they socialize with other students (t(30.313) = -5.197, p<0.001). This supports and extends our previous findings [22,23].…”
Section: Intersectionalitysupporting
confidence: 93%
“…The variation between 2017 and 2019 is discussed in our prior work [23]. It is worth noting that we observed that women who do not self-identify as being part of a minority had a very similar belongingness to non-minority men.…”
Section: Intersectionalitymentioning
confidence: 51%
See 3 more Smart Citations